Strategi dan Inovasi dalam Meningkatkan Akses Informasi Publik : (Studi di Kompas TV Medan) - Fariz Aditya; Raja Songkup Pratama; Yeni Yolanda Simbolon; Yuli Indriani Lubis; Halking Halking (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the strategies and digital innovations implemented by Kompas TV Medan in improving public access to information in the digital media ecosystem. Using a qualitative case study approach, the research explores newsroom practices, platform management, multimedia utilization, and data-driven decision-making in content production. The findings show that Kompas TV Medan has adopted a multiplatform newsroom model integrating television and digital content workflows to meet the growing demand for fast, accessible, and interactive information. Each digital platform Instagram, YouTube, TikTok, Facebook, and X is managed with distinct strategies tailored to audience characteristics. Data analytics guide editorial decisions, while creativity and visual optimization strengthen content engagement without compromising journalistic integrity. However, challenges such as limited digital human resources, uneven internet access, and competition with non-professional news accounts remain significant obstacles. Overall, Kompas TV Medan demonstrates adaptive and innovative capabilities in enhancing public information accessibility while supporting transparency and digital literacy in society.